(untitled) (Medico Legal Update, 2020)
Introduction: Stroke is a neurological condition that is one of the leading causes of death and disability in many low and middle income countries. However, many adjustable risk factors have become important. High blood pressure is the most common stroke risk factor globally as well as in our country, Basra. Objectives: To assess knowledge of patients with hypertension concerning prevention of cerebral vascular accident. To construct an instructional program for patients with hypertension concerning prevention of cerebral vascular accident. To evaluate the effectiveness of an instructional program on the knowledge of patients with hypertension concerning prevention of cerebral vascular accident. To know the association between level of knowledge the association between level of knowledge concerning prevention of cerebral vascular accident and socio-demographic variables. Methodology: : A quasi- experimental design (two group pre- test and post-test) was conducted in the present study which is carried out at Al-Razi Center in Al-Basra City from 8th of September 2019, to 16th of March, 2020. A non – probability (purposive) sample of (60) patients with hypertension were selected. Conclusion: There is significance need for educational program between (residency, type of family, duration of illness, habits and regularity of hypertension treatment) to prevention serious complication which stroke.